HUMAN RESOURCE DEVELOPMENT POLICIES FOR PWD (persons with disabilities) EMPLOYEES IN SOUTH CENTRAL RAILWAYS - Eslavath, Kiran Das Naik (The International Journal of Accounting and Business Society, 2019)
Service sector in India consists of a wide variety of services such as electricity, water supply, road, rail and air transport etc which provides a vast opportunities for HRD. Indian Railways is the backbone of service sector and one of the biggest employers in India. Indian Railways is one of the gigantic public undertakings enriched with fixed assets. The universe constitutes the PWD employees of South Central Railway.  The total universe of the organization is 1120 employees of various departments shown in table.  The sample size taken from the universe for the study is 50% i.e. 560 respondents. The analysis results that the most of the respondents are neutral in opinion in all the aspects of potential appraisal, career development and job rotation.  They disagree with some of the aspects of training and development, performance appraisal and promotions and transfers.  Keywords: Service Sector, Indian Railways, Human Resource Development.